HUBUNGAN KUALITAS PRODUK TERHADAP KEPUASAN PELANGGAN KERIPIK NENAS DI DESA KUALU NENAS KECAMATAN TAMBANG KABUPATEN KAMPAR PROVINSI RIAU - Dewi Sartika; Agustin Basriani (Procuratio : Jurnal Ilmiah Manajemen, 2018)
The purpose of this research is to know the relationship between variables of product quality that consists of working performance, reliability, features, resistance, suitability, and design with costumers’ satisfaction of pineapple crackers in kualu nenas village, tambang, Kampar regency, riau province. Tis research used quantitative method. Total populations in this research are 96 costumers, which mean they had bought pineapple crackers minimal twice in kualu nenas village. Analysis data technique used pearson correlation. And the results of this research are:1)There is positive relationship between working performance and costumers’ satisfaction of pineapple crackers in kualu nenas village, tambang. Kampar regency, Riau province.2)There is positive relationship between reliability and costumers satisfaction of pineapple crackers ini kualu nenas village, tambang, Kampar regency, Riau province,3)There is positive relationship between features and costumers’ satisfaction of pineapple crackers in kualu nenas village, tambang, Kampar regency, Riau province,4)There is positive relationship between suitability and costumers’ satisfaction of pineapple crackers in kualu nenas village, tambang, Kampar regency, Riau province,5) There is positive relationship between suitability and costumers of pineapple crackers satisfaction kualu nenas village, tambang, Kampar regency, Riau province,6)There is positive relationship between design with costumers of pineapple crackers satisfaction in kualu nenas village, tambang, Kampar regency, Riau province. Tujuan dari penelitian ini untuk mengetahui hubungan antara variabel-variabel kualitas produk yang terdiri dari kinerja, kehandalan, fitur, daya tahan, kesesuaian dan desain terhadap kepuasan pelanggan keripik nenas di Desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar Provinsi Riau. Penelitian ini menggunakan metode kuantitatif. Jumlah populasi dalam penelitian ini adalah 96 orang pelanggan,yaitu yang telah melakukan pembelian keripik nenas minimal 2 kali di Desa Kualu Nenas. Teknik Analisis data dengan menggunakan korelasi Pearson. Adapun hasil penelitian menunjukkan bahwa:1) Terdapat hubungan positif antara kinerja dengan kepuasan pelanggan keripik nenas di desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar Provinsi Riau; 2) Terdapat hubungan positif antara kehandalan dengan kepuasan pelanggan keripik nenas di desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar Provinsi Riau;3) Terdapat hubungan positif antara fitur dengan kepuasan pelanggan keripik nenas di desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar Provinsi Riau;4) Terdapat hubungan positif antara daya tahan dengan kepuasan pelanggan keripik nenas di desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar Provinsi Riau;5) Terdapat hubungan positif antara kesesuaian dengan kepuasan pelanggan keripik nenas di desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar Provinsi Riau;6) Terdapat hubungan positif antara desain dengan kepuasan pelanggan keripik nenas di desa Kualu Nenas Kecamatan Tambang Kabupaten Kampar Provinsi Riau.